2012
DOI: 10.1149/2.058302jes
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrochemistry of NaxFexMn1-xO2(1.0 ≤ x ≤ 0.5) for Na-Ion Battery Positive Electrodes

Abstract: The primary objective of research activities in Na-ion battery development is the implementation of inexpensive, sustainable and environmentally friendly battery materials. Here we report an investigation of Na x Fe x Mn 1-x O 2 electrode materials which contain elements commonly found in the earth's crust, have very low toxicity and cost, and can be prepared in open air atmosphere using simple procedures. Samples with x > 0.65 were found to have the same structure as O3 α-NaFeO 2 under selected synthesis cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 11 publications
12
116
1
Order By: Relevance
“…8,13,22,23 Fe 4+ in this compound was observed by Yue et al, 18 and other work also showed oxidation of Fe 3+ to Fe 4+ below 4 V. 6,8,13 We found the latter in Figure S1. Thus, the reversible and irreversible plateaus at 2.8 and Figure 3c may originate from the O3-P3 transition and Fe 4+ migration, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…8,13,22,23 Fe 4+ in this compound was observed by Yue et al, 18 and other work also showed oxidation of Fe 3+ to Fe 4+ below 4 V. 6,8,13 We found the latter in Figure S1. Thus, the reversible and irreversible plateaus at 2.8 and Figure 3c may originate from the O3-P3 transition and Fe 4+ migration, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…6 The charged state stability of the layered structure, and thereby their electrochemical properties, 7 can be enhanced by partially substituting Fe into redox-inactive elements and/or other transition metals. [8][9][10][11] Li et al proposed an optimal Fe content (< ∼33%) that promotes Na diffusion at the high state of charge. 12,13 Here, we use Ti 4+ as a structural stabilizer and report an O3-type 14 Na transition metal oxide (O3-NaMO 2 ) composition, NaTi 0.25 Fe 0.25 Co 0.25 Ni 0.25 O 2 (TFCN), for the optimized Fe redox activity.…”
mentioning
confidence: 99%
“…O3-type Na[Fe 1/2 Mn 1/2 ]O 2 can also be synthesized by controlling the ratio of Na/(Fe and Mn). [158] In contrast with P2 phase, large polarization (>1 V) during charge and discharge processes is observed for O3-type Na[Fe 1/2 Mn 1/2 ]O 2 when the Na cell is cycled in the voltage range of 1.5-4.25 V. [167] Interestingly, the synthesis of P2-and O3-Na 2/3 [Fe 2/3 Mn 1/3 ]O 2 with the same stoichiometry, which not only allowed a direct comparison of two phases for the first time, but also enabled some inferences to be made regarding the effect of phase on electrochemistry. In both phases, no Jahn-Teller structural distortion occurs due to the presence of high-spin octahedrally coordinated Fe 3+ (t 2g 3 e g 2 ) and Mn 4+ (t 2g 3 e g 0 ).…”
Section: Fe/mn-based Oxidesmentioning
confidence: 99%
“…[7] Obviously, due to the production cost of Li and its limited geographic distribution, the use of Li-ion batteries may be limited to hand held devices or electric vehicles, [8] and therefore, investigation regarding more abundant intercalation elements like Na + is inevitable. [9,10] Among many cathode candidates, Fe and Mn containing layered oxides have been investigated extensively, [11][12][13][14][15] because of advantages including environmental benignity, inexpensiveness, and large reversible capacity. Typical phases investigated are P2-and O3-phase where P2-phase has been synthesized as Na + deficient system (~0.67), and O3-phase has been prepared as fully sodiated system.…”
Section: Introductionmentioning
confidence: 99%